The Dimensions of Work Values in Islamic Social Financial Institutions Desired by Generation Y and Generation Z Digital Talents - Andi Hakim Kusuma; Ahmad Mukhlis Yusuf; Nur Hendrasto (Department Islamic Economics, 2023)
Maintaining sustainability and existence of Islamic social financial Institution in digital era requires technology adoption and digital talent readiness. But considering scarcity of digital talent in Indonesia, Islamic social financial institution needs to attract digital talent, especially generation Y and generation Z, by understanding desired dimensions of work values to join Islamic social financial institution. Based on previous studies, quantitative method is used to determine dimensions of work values desired by generation Y and generation Z to join Islamic social financial institution. This research find that income, career, and role model become the most desired dimensions of work values by generation Y and generation Z digital talents to join Islamic social financial institution.